2019
DOI: 10.1039/c9cy01421g
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical insight into the origin of the electrochemical promotion of ethylene oxidation on ruthenium oxide

Abstract: In EPOC the adsorption energies of the reactants and products are modified by applying an electrochemical potential to the catalyst. DFT computations unveil that the C–C and O–O bond dissociation are accelerated under positive and negative potential, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 81 publications
(91 reference statements)
3
40
0
Order By: Relevance
“…40 A more detail description of the corresponding methodology can be found here. 41 The transition states (TS) have been located as follows: the initial and final states were built by physisorption of molecules when necessary. Then, a rough nudged-elastic band (NEB) 42 computation with 8 images between the initial and final state was performed, seeded by linear interpolations between the two states.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 A more detail description of the corresponding methodology can be found here. 41 The transition states (TS) have been located as follows: the initial and final states were built by physisorption of molecules when necessary. Then, a rough nudged-elastic band (NEB) 42 computation with 8 images between the initial and final state was performed, seeded by linear interpolations between the two states.…”
Section: Computational Detailsmentioning
confidence: 99%
“…This scheme has been previously used by the authors for metallic surfaces and is well documented in the following references. [51][52][53] As discussed in the following paragraphs, this systematic selection results in several OER mechanisms, with overpotentials (η) that depend on whether the electrochemical potential is included at the CHE level (ηCHE) or through surface charging and a Poisson-Boltzmann electrolyte (ηPB).…”
Section: A Systematic Approach To Build the Reaction Pathmentioning
confidence: 99%
“…Due to pre-treatments and tests under oxygen-based reaction atmospheres, the noble metal nanoparticles are oxidized to RuO 2 and IrO 2 as demonstrated in previous studies using density functional theory (DFT) [34] and X-Ray Photoelectron Spectroscopy (XPS). [35] Furthermore, to check on the formation of nanoparticle noble metals, transmission electron microscopy (TEM) (JEOL JEM 2100F FETEM operating at 200 kV) was used for the TiO 2 -supported catalysts, and annular dark field Scanning TEM (STEM) (FEI Titan3 80-300 TEM operated at 300 kV) was used for the CeO 2 -based material.…”
Section: Experimental and Methods Sectionmentioning
confidence: 98%
“…Four-port valves were used to switch the feed inlet to the reactor between pre-treatment conditions and reactants feed. Another four-port valve would allow the feed gas to enter the reactor or by-pass it before it continues its flow to the Hiden® quadrupole mass spectrometer where the gas composition is detected by following the masses of 18,20,28,29,32,34,36,42,44, 46 m/z.…”
Section: Experimental and Methods Sectionmentioning
confidence: 99%
“…The linearized Poisson-Boltzmann equation with default parameters as implemented in VASPsol module [29] has been used to model the influence of the electrochemical potential at the catalyst surface [28,30]. For detailed explanations on the computational model, we refer the reader to ref [31], where we have also demonstrated that the precise technical parameters do not considerably influence the EPOC results. The investigated reaction pathway follows the proposal by Avanesian et al [3].…”
Section: Computational Detailsmentioning
confidence: 99%